Investigation among students’ and teachers’ perception of climate health awareness regarding low carbon ecofriendly practices - Natalia, Maryam; Ullah, Waheed; Khan, Ahsan Riaz; Wahid, Abdul; Mehmood, Muhammad Sajid; Naz, Madeeha (Frontiers in Environmental Science, 2023)
The study explores the awareness of climate change, perception and attitude towards nature, impacts, effects, hopes, responsibility and engagement in low carbon behavior among students (n=500) and faculty members (n=50) from universities in Multan city. Survey data was collected from non-environmental science departments (n=6). Results concluded that awareness of climate change is higher in teachers than students. Both respondents showed similar responses regarding their perception of issues, and impacts but showed discrepancy while selecting effects of climate change. Participants’ attitudes towards the environment and hope for mitigation are similar. Students and teachers believed that every sector has major responsibility except teachers agreed on full individual responsibility and international organization has a small portion of responsibility. Both participants showed no interest in engagement in low carbon activities. In the end need of future studies are also recommended to contribute to the database.